Pengaruh Harga Dan Promosi Terhadap Kepuasan Konsumen Sentra Laundry Di Sukatani Depok - Kusnul, Muhamad; Faisal Akbar, Mada (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. The purpose of this study is to determine the effect of price and promotion on consumer satisfaction at Sentra Laundry in Sukatani, Depok. This research uses a quantitative method with an associative approach. The population consists of all consumers of Sentra Laundry, and the sampling technique used is a saturated sample, resulting in a total of 100 respondents. Data were collected using a questionnaire. Data analysis includes validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing using SPSS version 27. The results indicate that the price variable has a significant effect on consumer satisfaction, with a significance level of 0.001 (< 0.05) and a t-value of 6.778 (> t-table 1.661). The promotion variable also has a significant effect on consumer satisfaction, with a significance level of 0.001 (< 0.05) and a t-value of 5.634 (> t-table 1.661). Simultaneously, price and promotion significantly influence consumer satisfaction, with a significance level of 0.001 (< 0.05) and an F-value of 205.209 (> F-table 3.09). The correlation coefficient test shows that the price variable has a very strong relationship with consumer satisfaction, with a correlation coefficient of 0.864, while promotion also has a very strong relationship with a coefficient of 0.848. The coefficient of determination (R²) is 0.805, indicating that price and promotion jointly influence consumer satisfaction by 80.5%, while the remaining 19.5% is influenced by other variables not examined in this study. The resulting multiple linear regression equation is: Y = -1.971 + 0.636X₁ + 0.420X₂ Keywords: Price, Promotion, Consumer Satisfaction